2007
DOI: 10.1111/j.1742-4658.2007.06133.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic degradation of nitric oxide synthase isoforms by calpain is modulated by the expression levels of HSP90

Abstract: Ca2+ loading of Jurkat and bovine aorta endothelium cells induces the degradation of the neuronal and endothelial nitric oxide synthases that are selectively expressed in these cell lines. For neuronal nitric oxide synthase, this process involves a conservative limited proteolysis without appreciable loss of catalytic activity. By contrast, endothelial nitic oxide synthase digestion proceeds through a parallel loss of protein and catalytic activity. The chaperone heat shock protein 90 (HSP90) is present in a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
54
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 52 publications
6
54
0
Order By: Relevance
“…In previous studies (16,17), we have demonstrated that in the presence of Ca 2ϩ , calpain can be recruited in a ternary complex containing eNOS, HSP90, and the protease. In this associated form, HSP90 and NOS become resistant to calpain digestion.…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…In previous studies (16,17), we have demonstrated that in the presence of Ca 2ϩ , calpain can be recruited in a ternary complex containing eNOS, HSP90, and the protease. In this associated form, HSP90 and NOS become resistant to calpain digestion.…”
mentioning
confidence: 90%
“…These observations could be explained on the basis of the well defined property of HSP90 to bind eNOS, forming discrete complexes (11,17,19). Similarly, we have previously observed -ionophore A23187 for 5 min at 37°C in the absence (ϩCa 2ϩ ) or in the presence of 2 mM Mg-ATP, together with 10 mM phosphoenolpyruvate and 2 g of purified pyruvate kinase (ϩCa 2ϩ ϩATP) were lysed, and aliquots (500 g of soluble protein) obtained as described under "Experimental Procedures" were incubated overnight at 4°C with monoclonal anti-HSP90 antibody.…”
Section: Enos Protection In Ca 2ϩmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, calpain systems appear to play key roles in angiogenesis 36,38) , wound closure 39) and maintenance of barrier functions 13,40) in ECs. In addition to motility responses, it has been reported that nitric oxide (NO) production in ECs is modulated through calpain-induced proteolysis of HSP90 42) or calpain-regulated PI3K/AMPK signaling 35) . The physiological significance of these calpain-mediated responses in ECs, however, remains controversial since the observations were mainly derived from cell-based experiments.…”
Section: Calpain and Vascular Integritymentioning
confidence: 99%